2021
DOI: 10.3390/rs13040705
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Top, Height and Photosynthetic Pigment Estimation Using Parrot Sequoia Multispectral Imagery and the Unmanned Aerial Vehicle (UAV)

Abstract: Remote sensing is one of the modern methods that have significantly developed over the last two decades and, nowadays, it provides a new means for forest monitoring. High spatial and temporal resolutions are demanded for the accurate and timely monitoring of forests. In this study, multi-spectral Unmanned Aerial Vehicle (UAV) images were used to estimate canopy parameters (definition of crown extent, top, and height, as well as photosynthetic pigment contents). The UAV images in Green, Red, Red-Edge, and Near … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 95 publications
3
14
0
Order By: Relevance
“…In recent decades, various sensors mounted on UAVs have been widely used to monitor crop growth traits such as LiDAR [54], hyperspectral [55] and multispectral [26] devices, NIR [56][57][58], and RGB cameras [59,60]. Compared to other sensors, the UAV-RGB camera was cheaper and lighter which made it possible for a longer working time to apply to larger areas in precision agriculture.…”
Section: Implications Of Uav-based Rgb Imagery For Crop Monitoringmentioning
confidence: 99%
“…In recent decades, various sensors mounted on UAVs have been widely used to monitor crop growth traits such as LiDAR [54], hyperspectral [55] and multispectral [26] devices, NIR [56][57][58], and RGB cameras [59,60]. Compared to other sensors, the UAV-RGB camera was cheaper and lighter which made it possible for a longer working time to apply to larger areas in precision agriculture.…”
Section: Implications Of Uav-based Rgb Imagery For Crop Monitoringmentioning
confidence: 99%
“…We focused on the effect of leaf developmental category and leaf phenology on VI linear model performance. The effect of leaf age on modelling of biophysical traits from spectra is currently a topical theme for evergreen conifers bearing several needle age classes at once [20,36,80]; and also tropical tree species with leaf developmental asynchrony [81,82]. Moreover, in some tropical trees with asynchronous leaf development and long leaf lifespan (e.g., 360 days), even the leaf age could be modelled from leaf spectra [83].…”
Section: Seasonal Course Of Leaf Optical Properties Related To Leaf D...mentioning
confidence: 99%
“…With the current wide availability of hyperspectral data at leaf and canopy levels, the multivariate approaches to leaf trait modelling, such as PLSR, exploiting the whole spectral range, are preferentially used [20,46,81]. Although our source data were hyperspectral, we built the present study on vegetation indices, which are still widely used due to rise of various affordable multispectral sensors [80,[94][95][96] or satellite multispectral data [97]. On a large scale, starting in 2015 thanks to a NASA initiative, the Harmonized Landsat and Sentinel-2 (HLS) surface reflectance data set represents a novel type of multispectral satellite data [98,99] and vegetation indices derived from HLS have potential to monitor land surface phenology [100].…”
Section: Effect Of Vegetation Indices Intercorrelationmentioning
confidence: 99%
“…The results showed that NDVI and red edge NDVI extracted by a multipectral UAV system could be used to estimate the PPC in a Norway spruce's individual tree canopy at a semiquantitative level. Furthermore, the needle age had a major influence on the estimation results, while the illumination conditions had little effect [23].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, no matter whether it is multispectral UAV or canopy PPC, the research on forestry is still immature (please refer to the Supplementary Materials), and there are still various problems that need to be further solved. Therefore, how to retrieve the PPC of forest canopy from multispectral UAV images becomes a quantitative remote sensing problem worthy of discussion at present [23].…”
Section: Introductionmentioning
confidence: 99%